The Potential of Sweet Starfruit as a Gastroprotector of Gaster Damage Due to Free Radicals - Alandra Rizhaqi Vastra; Mira Yustika Susilo; Neema Putri Prameswari; Bagus Pratama (GLOBAL HEALTH SCIENCE GROUP, 2020)
Gastric ulcer is a condition when deep gastric mucosa is damaged. This condition can be caused by oxidative stress which produces free radicals. Ulcer can be potentially prevented or treated with active substances contained by plants such as sweet starfruit. Sweet starfruit (Averrhoa carambola Linn) is a plant that has a high antioxidant effect with flavonoid content which plays a role in the process of gastric mucosal damage Objective to describe the potential gastroprotector effect of sweet starfruit (Averrhoa carambola Linn) in gastric damage caused by free radicals. This paper used literature study involving 18 libraries both national and international books and journal. Sweet starfruit (Averrhoa carambola Linn) contains flavonoid, this compound can work as an antioxidant by giving electrons to free radicals which causes the structure of free radicals to be more stable so that it can prevent the process of lipid peroxidase. Conclusions: Sweet starfruit has anti-ulcer potential effect with its antioxidant content which is flavonoids. Keywords: gastric ulcer, free radical, sweet starfruit, antioxidant